2023
DOI: 10.3389/fenvs.2023.1239288
|View full text |Cite
|
Sign up to set email alerts
|

The effect of technological innovations, urbanization and economic growth on environmental quality: does governance matter?

Hayat Khan,
Itbar Khan

Abstract: Climate change has become a major challenge in recent decades as a result of rapid economic growth due to increased energy use and a rise in urbanization. Environmental damage induced by energy use, urbanization, and economic growth can be overcome by technological advancement and good governance. This study examines the effect of urbanization, technological innovations, and economic growth on carbon dioxide emissions in the Belt and Road initiative countries from 2002 to 2022. By using GMM model, the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 129 publications
1
1
0
Order By: Relevance
“…Specifically, Claire and Widyawati (2023) and Patel and Mehta (2023) support our choice of industrialization as a predictor of environmental quality, while Ren et al (2023) and Tao et al (2023) collaborate with our adoption of financial development as a determinant of environmental quality. In addition, Chiu and Zhang (2023) and Wang et al (2023) agree with our choice of foreign direct investment as a predictor of environmental quality, while Khan and Khan (2023) and Luqman et al (2023) align with our choice of urbanization as a determinant of environmental quality. Finally, González-Álvarez and Montañés (2023) and Li et al (2023) support our adoption of energy consumption as a factor that explains environmental quality in economies.…”
Section: Data Source and Descriptive Statisticssupporting
confidence: 63%
See 1 more Smart Citation
“…Specifically, Claire and Widyawati (2023) and Patel and Mehta (2023) support our choice of industrialization as a predictor of environmental quality, while Ren et al (2023) and Tao et al (2023) collaborate with our adoption of financial development as a determinant of environmental quality. In addition, Chiu and Zhang (2023) and Wang et al (2023) agree with our choice of foreign direct investment as a predictor of environmental quality, while Khan and Khan (2023) and Luqman et al (2023) align with our choice of urbanization as a determinant of environmental quality. Finally, González-Álvarez and Montañés (2023) and Li et al (2023) support our adoption of energy consumption as a factor that explains environmental quality in economies.…”
Section: Data Source and Descriptive Statisticssupporting
confidence: 63%
“…Hussain et al (2023) supported this finding by confirming urbanization as harmful to environmental quality in 54 African nations, while Opoku Marfo et al ( 2023) reported a similar finding for Ghana. However, Khan and Khan (2023) found a nonlinear relationship between urbanization and environmental pollution in Belt and Road Initiative countries, while Tawfeeq (2023) discovered a negative association between urbanization and CO 2 emissions in the United States.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…However, the authors also caution against potential pitfalls, including privacy concerns and the risk of over-reliance on technology, which could undermine the effectiveness of governance efforts (Ajala and Balogun, 2024). Khan and Khan (2023) delve into the effects of technological innovations on environmental quality, within the context of urbanization and economic growth. Their study underscores the dual role of technology as both a contributor to and a mitigator of environmental degradation.…”
Section: Technological Innovations and Their Impact On Governancementioning
confidence: 99%
“…The dataset includes measurements of carbon monoxide (CO), sulfur dioxide (SO 2 ), nitrogen oxides (NOx), oxygen (O 2 ), and dust levels, along with temperatures recorded. For this analysis, deep learning methods such as multilayer perceptron network (MLP) and long short-term memory (LSTM) models were used, while machine technological developments, population growth, and urbanization (Dai et al, 2022;Fontes et al, 2014;Khan & Khan, 2023;Li et al, 2019). Significant environmental problems, such as the greenhouse effect, occur with the increase in energy consumption (Cui et al, 2023;Dong et al 2022a, b;Hu et al, 2024;Khan & Khan, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…For this analysis, deep learning methods such as multilayer perceptron network (MLP) and long short-term memory (LSTM) models were used, while machine technological developments, population growth, and urbanization (Dai et al, 2022;Fontes et al, 2014;Khan & Khan, 2023;Li et al, 2019). Significant environmental problems, such as the greenhouse effect, occur with the increase in energy consumption (Cui et al, 2023;Dong et al 2022a, b;Hu et al, 2024;Khan & Khan, 2023). In particular, coal-fired thermal power plants both play an active role in energy production and cause environmental problems due to the use of fossil fuels (Hu et al, 2024;Kasman & Duman, 2015;Munawer, 2018;Osobajo et al, 2020;Song et al 2021a, b).…”
Section: Introductionmentioning
confidence: 99%